Meningkatkan Minat Baca Di Era Digitalisasi Melalui Perpustakaan Jalanan Askara Aksara - Nirwana, Baiq Nadia; Marswandi, Ega Dwi Putri; Maulani, Maghfira Rizky; Wardi, Putri Amalia; Wiguna, Saka Pawica (CV. Global Cendekia Inti, 2023)
The shift of the era toward digitalization has had a significant impact on public reading interests, especially among the digital generation. In this context, this community dedication aims to boost the interest in reading through an innovation by opening up a library of paths. The method of activity is community development that is named after the Askara Aksara street library program. The Character Soldier was designed as a street library that made dedication participants discover new things about books and reading. This approach is expected to increase public accessibility and involvement in literacy in the midst of the digital information stream. Based on the results of interviews with dedicated participants, the implementation of Askara Aksara has been successful in raising public interest in reading, especially among the digital generation. This success can be seen in increased frequency of visits, participation in literacy activities, and changes in reading behavior. Soldiers of Characters is expected to be an inspiring model for the development of street libraries in various communities, presenting innovative solutions to strengthen literacy amid the dynamic change of information technology.